Time to first positive HIV-1 DNA PCR may differ with antiretroviral regimen in infants infected with non-B subtype HIV-1 - Raji Balasubramanian (2018)
Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved. Objective: To evaluate the association of type and timing of prophylactic maternal and infant antiretroviral regimen with time to first positive HIV-1 DNA PCR test, in nonbreastfed HIV-infected infants, from populations infected predominantly with HIV-1 non-B subtype virus. Design: Analysis of combined data on nonbreastfed HIV-infected infants from prospective cohorts in Botswana, Thailand, and the United Kingdom (N=405). Methods: Parametric models appropriate for interval-censored outcomes estimated the time to first positive PCR according to maternal or infant antiretroviral regimen category and timing of maternal antiretroviral initiation, with adjustment for covariates. Results: Maternal antiretroviral regimens included: no antiretrovirals (n=138), single-nucleoside analog reverse transcriptase inhibitor (n=165), single-dose nevirapine with zidovudine (n=66), and combination prophylaxis with 3 or more antiretrovirals [combination antiretroviral therapy (cART), n=36]. Type of maternal/infant antiretroviral regimen and timing of maternal antiretroviral initiation were each significantly associated with time to first positive PCR (multivariate P<0.0001). The probability of a positive test with no antiretrovirals compared with the other regimen/timing groups was significantly lower at 1 day after birth, but did not differ significantly after age 14 days. In a subgroup of 143 infants testing negative at birth, infant cART was significantly associated with longer time to first positive test (multivariate P=0.04). Conclusion: Time to first positive HIV-1 DNA PCR in HIV-1-infected nonbreastfed infants (non-B HIV subtype) may differ according to maternal/infant antiretroviral regimen and may be longer with infant cART, which may have implications for scheduling infant HIV PCR-diagnostic testing and confirming final infant HIV status.